Polska w GATT/WTO - Skrzypczyńska, Joanna (Przegląd Politologiczny, 2018)
The purpose of the paper is to analyze the position of Poland in the GATT and WTO. Another topic concerns the principles of the Common Commercial Policy of the European Union, including Poland after accession. The first part of the paper presents the position of Poland in the GATT, with particular emphasis on Poland’s specific membership, which followed from its centrally planned economy. The second part of the paper concentrates on the issue of Poland’s functioning within the WTO and Polish postulates in the Development Round (Doha) of the WTO in the context of liberalized trade of agricultural commodities. The effects of excessive imports from China are also analyzed from the point of view of Polish producers of soft fruit and in terms of anti-dumping duties imposed by the EU on such imports.